2019
DOI: 10.1002/ejoc.201801799
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Catalytic Enantioselective Rearrangement

Abstract: Among the fundamental chemical transformations in organic synthesis, rearrangement has been recognized as powerful and reliable reactions for the construction of carbon–carbon or carbon–heteroatom bonds. Benefiting from the advance of the novel catalytic system, catalyst design and activation mode, the chemistry of enantioselective rearrangements has experienced ever‐growing development recently and has been successfully used in the synthesis of chiral non‐racemic building blocks, natural products, and other v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 150 publications
0
40
0
Order By: Relevance
“…[78] The rapid growth in each of this reaction classification by gold catalysis inspired several research groups around the world to summarize important updates on this field. [79][80][81][82][83][84][85][86][87][88][89][90] Within the broad landscape of gold catalysis in reaction chemistry, the dexterity of gold catalysis to effect molecular rearrangements will be the main focus of this review. Indeed, increasing the molecular complexity by gold catalyzed rearrangements is quite advantageous over other catalytic methods; [91][92][93][94][95] in terms of scope towards diverse rearrangements, well-understood reactivity pattern, mildness of the process, and excellent selectivities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[78] The rapid growth in each of this reaction classification by gold catalysis inspired several research groups around the world to summarize important updates on this field. [79][80][81][82][83][84][85][86][87][88][89][90] Within the broad landscape of gold catalysis in reaction chemistry, the dexterity of gold catalysis to effect molecular rearrangements will be the main focus of this review. Indeed, increasing the molecular complexity by gold catalyzed rearrangements is quite advantageous over other catalytic methods; [91][92][93][94][95] in terms of scope towards diverse rearrangements, well-understood reactivity pattern, mildness of the process, and excellent selectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Au(I)‐ ligated with supramolecular cages also emerged as an excellent catalytic system for controlling the reactivity and selectivity of several organic reactions [78] . The rapid growth in each of this reaction classification by gold catalysis inspired several research groups around the world to summarize important updates on this field [79–90] . Within the broad landscape of gold catalysis in reaction chemistry, the dexterity of gold catalysis to effect molecular rearrangements will be the main focus of this review.…”
Section: Introductionmentioning
confidence: 99%
“…As the development of semipinacol rearrangement in the last two decades has gradually become mature, summarization of a certain aspect of the venerable reaction has been documented in several previous reviews. [2][3][4][5][14][15][16][17] Nonetheless, recent advances of semipinacol rearrangement in terms of novel electrophiles, radical processes, 4 tandem reactions, and catalytic Xiao-Ming Zhang studied chemistry at Lanzhou University where he received his B.S. in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Baran et al reported an elegant synthesis of hindered dialkyl ethers with electrogenerated carbocations generated from alkyl carboxylic acids 23 , which demonstrates the power of electrochemistry to substantially improve the synthetic efficiency [24][25][26][27][28][29][30][31][32][33][34] . Rearrangement reactions through a molecular skeletal reorganization are powerful chemical transformations for generating structural complexity and diversity [35][36][37][38][39] . Based on our research experience in the development of C-C or C-X bond forming methodologies via electrochemistry [40][41][42] , we envisioned that the in situ or isolated hydrazides, prepared from diverse alkyl carboxylic acids and 2-hydrazinopyridines, might undergo an atom/ step-economical rearrangement to afford those otherwiseinaccessible triazolopyridinone derivatives under metal and external oxidant free electrochemical conditions (Fig.…”
mentioning
confidence: 99%